Bidirectional ventricular tachycardia due to digoxin-diuretic interaction in post-cardiac surgery patient: a case report - Alanís-Naranjo, José Martín (2024)
Bidirectional ventricular tachycardia (BVT) is a rare form of malignant ventricular arrhythmia characterized by beat-to-beat alternation in the QRS axis. BVT is a hallmark of digitalis toxicity, but digoxin-induced BVT secondary to digoxin-diuretic interaction in cardiac surgery patients is not widely reported. We present the case of a 62-year-old woman undergoing mitral valve replacement with tricuspid annuloplasty who developed postoperative congestive heart failure and vasoplegic syndrome requiring norepinephrine, vasopressin, and loop diuretics. During postoperative care, she presented atrial fibrillation with rapid ventricular response, achieving rate control with digoxin, but later displayed hemodynamically stable BVT associated with digitalis toxicity. The case highlights the importance of physicians monitoring digoxin toxicity when prescribing digoxin to patients with a diuretic regimen, particularly loop diuretics. During digoxin-induced-BVT, supportive treatment, including discontinuing digitalis coupled with potassium and magnesium supplements, can be considered as long as digoxin-specific antibodies are unavailable, and the patient is hemodynamically stable.